Participatory rangeland management (PRM): The case of Kenya and Tanzania - Mukalo, Irene Aloo (ILRI, 2023)
A presentation on the experiences of applying participatory rangeland management (PRM) in Kenya and Tanzania and opportunities for spillover and scaling up. PRM is being implemented by AICCRA and the Initiative on Livestock and Climate.